Complications following orthognathic surgery for patients with cleft lip/palate: A systematic review - Kazuaki Yamaguchi; Daniel Lonic; Lun-Jou Lo (Journal of the Formosan Medical Association, 2016)
The purpose of this systematic review is to update the available data for complications following orthognathic surgery in cleft lip and/or palate patients. Methods: Three electronic databases (Medline, Embase, and Cochrane) were searched for publications from 1990 to 2014. Results: A total of 26 articles were selected including 1003 patients (male: 391, female: 353, 259: not mentioned) who underwent maxillary osteotomies for cleft lip/palate. Mean age at surgery was 19.3 years (range: 8.5–60 years). Overall perioperative complications were reported in 126 cases (12.76%). The most common complication was closure failure of pre-existing palatal fistula (28.57%), followed by velopharyngeal impairment (16.79%), closure failure of pre-existing alveolar fistula (10.74%), gingival recession (4.55%), and failure of premaxilla stabilization in bilateral cases (4.55%). Severe vascular complications included one arteriovenous fistula (0.10%), one maxillary aneurysm (0.10%), and one cavernous sinus thrombosis (0.10%). Mean horizontal relapse rate was 17.9% (range: −20.0% to 37.2%), and mean vertical relapse rate was 35.4% (range: −25.9% to 162.5%). Reoperation rate was 12.2% (range: 0.0–64.0%). Prospective studies or randomized trials were rare. Conclusion: To obtain a dataset with higher evidence, a prospective multicenter study should be conducted with clearly defined criteria for each complication.